Eglise de Tourane (Annam) - 1924 - Uncredited author. (Wikimedia Commons, 1924)
Carte postale ancienne issue de Wikimedia Commons. Titre: Eglise de Tourane (Annam) - 1924. A Roman-Catholic Church in the Annamese city of Tourane, French Indo-China.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; église